Sugar-sweetened beverages (SSBs) consumption of high school students in two selected public schools of Manila City District V - Cañete, Joan Claire N.
Objective: To describe the sugar-sweetened beverages (SSBs) consumption of high school students in two selected public schools of Manila City District V.